Pragas invasivas da soja no Brasil e o caso da mosca-da-haste, Melanagromyza sojae: diversidade genética na América do Sul - Pozebon, Henrique (2021)
Soybean production in Brazil has been historically affected by exotic arthropod pests, whose introduction leads to severe economic and ecological damage. However, precise estimates of economic impacts resulted from such invasions are lacking. The stem fly Melanagromyza sojae (Zehntner, 1900) (Diptera: Agromyzidae), recently introduced and established in the soybean belt of South America, poses a considerable threat to soybean production in the continent due to its high damaging potential, remaining unexplored regarding genetic traits. This work comprises two chapters aimed at assessing the impact of invasive pests on Brazilian soybean production, identifying potential future invaders; and unravelling the current scenario of M. sojae invasion in South America, genetically characterizing populations of this pest from Brazil, Bolivia, Paraguay and Argentina. The first chapter revealed that Bemisia tabaci MEAM1, Tetranychus urticae and Helicoverpa armigera introductions in Brazil led to a threefold increase in insecticide usage from 1990 to 2016, based on a review of literature and analysis of historical data from the FAO statistical database. By evaluating four criteria related to potential invasiveness of arthropod pests (i.e. likelihood of entry, likelihood of establishment, biological traits and availability of management measures), the yet absent species Aphis glycines and Spodoptera litura were identified as high-risk potential invaders to Brazil, whereas the already established M. sojae is likely to increase its occurrence. The second chapter included the characterization of mtCOI gene in 79 M. sojae individuals from Rio Grande do Sul, Santa Catarina, Goiás, Paraguay, Bolivia and Argentina, revealing that 22 different M. sojae haplotypes are present in the continent. Specimens sampled during the 2018/19 cropping season underwent morphological identification, DNA extraction, amplification by PCR and sequencing of the mtCOI gene. The resulting sequences were analysed in specific softwares, together with M. sojae sequences previously published and available on GenBank. Haplotype Msoj-COI-02 was the most frequent in South America, followed by Msoj-COI-01, and is probably the ancestral haplotype from which the other strains have originated. Furthermore, novel haplotypes Msoj-COI-21, Msoj-COI-22 and Msoj-COI-23 were identified for the first time in Rio Grande do Sul. The high genetic diversity found suggests that multiple introductions of M. sojae female founders took place in South America, highlighting the need to strengthen biosecurity barriers and develop economically efficient and environmentally sustainable management programs for this highly invasive pest.